(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In article influence of parasitic invasion Ergasilus sieboldi on reproductive potential of 4 kinds Gobiidae’s fishes were considered. The short characteristic of biology, morphology and life cycle of this parasite were given. It was shown that the greatest contamination of Gobiidae’s fishes were observed during the summer period when the water temperature optimal (20 °-25 °) for reproduction and development Ergasilus sieboldi by the autumn contamination of fishes parasites decreases. It was established that males Gobiidae’s fishes for whom the care of posterity is characteristic are more subject to an attack ofparasites: they protect the laying up for emerging larvae and consequently are inactive